2011
DOI: 10.3758/s13423-011-0113-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of testing on learning of functions

Abstract: Is learning of a complex functional relationship enhanced by trying to predict what output will go with a given input, as compared to studying an input-output pair? We examined learning of a bilinear function and transfer to new items outside the trained range. Subjects either saw the input-output pairs (study-only condition) or attempted to guess the output and then saw the pair (test/study condition). The total study times were equated, and motivation was enhanced with a monetary bonus. Performance was marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 24 publications
2
43
0
Order By: Relevance
“…In a recent study, Kang, McDaniel, and Pashler (2011) demonstrated that testing can enhance transfer of mathematical function learning. Participants learned the relationship between x and y values either by seeing the two values side by side (i.e., pure study) or by attempting to estimate y given x before seeing the correct y value (i.e., test with feedback).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Kang, McDaniel, and Pashler (2011) demonstrated that testing can enhance transfer of mathematical function learning. Participants learned the relationship between x and y values either by seeing the two values side by side (i.e., pure study) or by attempting to estimate y given x before seeing the correct y value (i.e., test with feedback).…”
Section: Discussionmentioning
confidence: 99%
“…Testing enhances the transfer of learning from the specific questions from practice to new problems [63,[65][66][67], enhances re-learning of information [68], and results in higher exam scores [57].…”
Section: (3) the Testing Effect Generates Transfer Of Learningmentioning
confidence: 99%
“…We included only studies that used a restudy control condition, because even though the term testing effect is also used to refer to beneficial effects of testing as an additional activity (e.g., McDaniel et al 2011;Smith and Karpicke 2014), any beneficial effects of testing as an additional activity could be due to increased time on task rather than the retrieval activity itself. Moreover, we only included studies that reported effects on a delayed final test, because even though some studies have shown testing effects on immediate final tests taking place shortly after the study/restudy or study/test phase (e.g., Carpenter 2009;Carpenter and DeLosh 2006;Carpenter and Kelly 2012;Kang et al 2011;Verkoeijen et al 2012), it has been shown that the testing effect often only becomes apparent at a delay of a couple of days or more, with restudy initially, being as, or sometimes even more, effective (e.g., Roediger and Karpicke 2006a;Wheeler et al 2003).…”
mentioning
confidence: 99%